Ermeni Kıpçakçasında Olumsuzluk Şekilleri - Kutalmış, Mehmet (Gökkubbe, 2004)
Armenians since the 13. century have intensive cultural relations with Kipchak Turks in Crimea. As a result of intensive contacts adopted Armenians Kipchak Turkish, spoke Kipchak at their homes, prayed in Kipchak at their churchs; written and published Kipchak works in Armenian script. The aim of the research is after determining the negativity forms in the Armeno-Kipchak to examine their ways of usage, functions and differences of meaning. Besides, the effect of Armenian and Russian negativity forms to the negativity category in the Armenian Kipchak will be touched. Comparisons with the other Kipchak dialects will be made where necessary. In this essay those negativity forms existing in the Armeno-Kipchak are examined: 1. Negativity suffixes: -MA- and -slz-. 2. Negativity prepositions: YOK and DEGÜl. 3. Forms meaning negativity: ne ... ne ...
Negative Forms in the Armeno-Kipchak
Keywords: Kipchak; Armenian; Negativity; -MA; -Slz-; YOK; DEGÜI; Ne ... Ne ...